Poverty Reduction And Growth Trust : 2020 Borrowing Agreements With The National Bank Of Belgium, Banco Central Do Brasil, Banque De France, The Government Of Japan, De Nederlandsche Bank NV, The Norwegian Ministry Of Finance Representing The Kingdom Of Norway, The Bank Of Spain, The Sveriges Riksbank And The Government Of The United Kingdom. (Policy Papers; Policy Paper ;, 2020)
This paper presents the first set of Poverty Reduction and Growth Trust (PRGT) borrowing agreements that have been signed to respond to the unprecedented demand for concessional financing during the COVID-19 pandemic. A fast-track loan mobilization round has been instrumental to allow the Fund to raise access limits and scale up emergency financing to low-income countries (LICs). The new agreements and augmentations of existing agreements that have been finalized are from Belgium, Brazil, France, Japan, the Netherlands, Norway, Spain, Sweden and the United Kingdom. Together, these agreements provide a total of SDR 10.6 billion in new PRGT loan resources for LICs.